PERFORMANCE ANALYSIS OF HORTICULTURE SUPPLY CHAIN MANAGEMENT AT CV.MIRACLE KURNIA FARM KABUPATEN SIDOARJO - Maulidina Naafilah; Mubarokah; Ika Sari Tondang (RADJA PUBLIKA, 2024)
Supply chain management is the planning, design and control of the flow of information and goods along the supply chain with the aim of meeting customer requirements efficiently for the present and the future. CV. Miracle Kurnia Farm is a company operating in the horticultural agribusiness sector and there have been several problems related to supply chain management, including delivery delays, limited inventory, and problems in product quality control. The aim of this research is to describe supply chain management and analyze supply chain performance in horticultural farming at CV. Miracle Kurnia Farm. The research results showed that the value of supply chain performance at CV. Miracle Kurnia Farm showed a result of 85.4, supply chain performance is classified as good. Factors such as good planning, efficient resource management, orderly logistics distribution and efficient returns handling have contributed to the overall optimal performance. This value reflects success in managing the horticultural supply chain, supporting business sustainability, and ensuring customer satisfaction.